Relationships between antibodies to native DNA and glomerulonephritis in systemic lupus erythematosus. - Tron, F (1977)
Anti-native DNA antibodies have been evaluated in forty-six lupus patients' sera for antigen-binding capacity, affinity and precipitating activity. Diffuse proliferative glomerulonephritis was significantly correlated with the presence of high serum level of free anti-native DNA antibodies. Weak affinities were more often found in patients with than without glomerular changes but several patients had high-affinity anti-DNA antibodies and severe glomerulonephritis. No correlation was found between anti-DNA antibody-precipitating activity and renal lesions.